2004
DOI: 10.1142/s0219199704001501
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Yamabe Flow on Surfaces

Abstract: In this paper we develop an approach to conformal geometry of piecewise flat metrics on manifolds. In particular, we formulate the combinatorial Yamabe problem for piecewise flat metrics. In the case of surfaces, we define the combinatorial Yamabe flow on the space of all piecewise flat metrics associated to a triangulated surface. We show that the flow either develops removable singularities or converges exponentially fast to a constant combinatorial curvature metric. If the singularity develops, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
267
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(271 citation statements)
references
References 11 publications
4
267
0
Order By: Relevance
“…Iterative? Shape-preserving [6] Fixed Yes No MIPS [16] Free Yes Yes ABF/ABF++ [33,34] Free Local (no flips) Yes LSCM/DNCP [4,23] Free No No Holomorphic 1-form [12] Fixed No No Mean-value [7] Fixed Yes No Yamabe Riemann map [26] Fixed Yes Yes Circle patterns [22] Free Local (no flips) Yes Genus-0 surface conformal map [19] Free No Yes Discrete Ricci flow [20] Fixed Yes Yes Spectral conformal [27] Free No No Generalized Ricci flow [36] Fixed Yes Yes Two-step iteration [3] Fixed Yes Yes [13] and an iterative scheme for genus-0 surface conformal mapping in [12] to obtain a planar conformal parameterization. In [27], Mullen et al reported a spectral approach to discrete conformal parameterizations, which involves solving a sparse symmetric generalized eigenvalue problem.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iterative? Shape-preserving [6] Fixed Yes No MIPS [16] Free Yes Yes ABF/ABF++ [33,34] Free Local (no flips) Yes LSCM/DNCP [4,23] Free No No Holomorphic 1-form [12] Fixed No No Mean-value [7] Fixed Yes No Yamabe Riemann map [26] Fixed Yes Yes Circle patterns [22] Free Local (no flips) Yes Genus-0 surface conformal map [19] Free No Yes Discrete Ricci flow [20] Fixed Yes Yes Spectral conformal [27] Free No No Generalized Ricci flow [36] Fixed Yes Yes Two-step iteration [3] Fixed Yes Yes [13] and an iterative scheme for genus-0 surface conformal mapping in [12] to obtain a planar conformal parameterization. In [27], Mullen et al reported a spectral approach to discrete conformal parameterizations, which involves solving a sparse symmetric generalized eigenvalue problem.…”
Section: Methodsmentioning
confidence: 99%
“…By integrating the holomorphic 1-forms on a mesh, a globally conformal parameterization can be obtained. In [26], Luo proposed the combinatorial Yamabe flow on the space of all piecewise flat metrics associated with a triangulated surface for the parameterization. In [20], Jin et al suggested the discrete Ricci flow method for conformal parameterizations, based on a variational framework and circle packing.…”
Section: Methodsmentioning
confidence: 99%
“…discrete) variant of the Ricci flow by Chow and Luo [7] (see also [16]). In their paper the surface is triangulated, and the metric is given as a function which assigns to each vertex v i (i = 1, .…”
Section: Remarks Concerning Related Workmentioning
confidence: 99%
“…It is motivated by Thurston's circle packings as a discrete analog of holomorphic functions [34]. Another version of discrete conformality is based on conformal equivalence of triangle meshes [29,39], where the conformal structure is defined by the length cross ratios of neighboring triangles. Luo introduced this notion when studying a discrete Yamabe flow.…”
Section: Introductionmentioning
confidence: 99%
“…Note that Theorem 1.4 concerns the theory of conformal equivalence of triangle meshes [29,39] while Theorem 1.5 deals with the notion of circle patterns [36].…”
Section: Introductionmentioning
confidence: 99%